2006
DOI: 10.1111/j.1537-2995.2006.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of transmissible spongiform encephalopathy infectivity from human red blood cells with prion protein affinity ligands

Abstract: If endogenous TSE infectivity in RBCs binds to the ligands in the same proportion as brain-derived infectivity spiked into RBCs, the four most effective ligands would remove 3 to 4 log ID(50) per mL. A follow-up experiment is in progress to test whether endogenous blood-borne infectivity is also reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 9 publications
3
74
0
Order By: Relevance
“…Moreover, the infectivity associated with S HS was not removed by leukodepletion from whole blood and red blood cells, further confirming its soluble nature and its presumed biophysical similarity to the endogenous soluble plasma-associated infectivity [10]. This soluble S HS -associated infectivity could represent the same form of prion infectivity previously described by Gregori et al [16,17] as the portion of the TSE infectivity present in a brain spike that could not be removed during validation studies for prion removal from blood.…”
Section: Introductionsupporting
confidence: 73%
“…Moreover, the infectivity associated with S HS was not removed by leukodepletion from whole blood and red blood cells, further confirming its soluble nature and its presumed biophysical similarity to the endogenous soluble plasma-associated infectivity [10]. This soluble S HS -associated infectivity could represent the same form of prion infectivity previously described by Gregori et al [16,17] as the portion of the TSE infectivity present in a brain spike that could not be removed during validation studies for prion removal from blood.…”
Section: Introductionsupporting
confidence: 73%
“…In our laboratory the concentration of 263K scrapie in the brains of hamsters in the late stages of symptomatic disease is consistently between 1 and 2×10 10 Infectious Dose 50 /g of brain [23]. In the absence of amplification, a 10 10 dilution of 263K brain would contain 1 ID 50 /ml giving a probability of infection of 0.05 from a 50 µl inoculation [23]. Nevertheless, all animals inoculated with PMCA products formed in the presence or absence of beads developed clinical disease with the mean value of endpoint 108.6±3.9 or 114.2±6.3 days post inoculation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The final dilution of the initial 263K brain material was 10 10 fold. In our laboratory the concentration of 263K scrapie in the brains of hamsters in the late stages of symptomatic disease is consistently between 1 and 2×10 10 Infectious Dose 50 /g of brain [23]. In the absence of amplification, a 10 10 dilution of 263K brain would contain 1 ID 50 /ml giving a probability of infection of 0.05 from a 50 µl inoculation [23].…”
Section: Resultsmentioning
confidence: 89%
“…A red cell filter device, P-Capt (Macopharma, Tourcoing, France), incorporating a specific resin designed to remove prions (Gregori et al, 2006), the infectious agent in blood thought to cause vCJD, was CE marked in Europe in 2006. P-Capt filtered red blood cell concentrates (PF-RCC) behaved normally in laboratory assays and had a normal antigenic profile (Murphy et al, 2009), and a study in 20 patients showed that exposure to 1-2 PF-RCC units did not generate any attributable adverse events (Cahill et al, 2010).…”
mentioning
confidence: 99%